Dynamics of Timely Vaccination Among Tender-Age Infants in two Subjects of Russian Federation with the Lowest Immunization Coverage in 2020: Serial Cross-Sectional Study - Radima A. Mukozheva; Tatyana V. Kulichenko; Liudmila Yu. Semavina; Vera I. Bosikova; Alexandra V. Uarova ("Paediatrician" Publishers LLC, 2024)
Background. It was revealed in 2020 that immunization of children in decreed times in several subjects of Russian Federation was below the standard level. Therefore, monitoring of timely vaccination in children of these regions was relevant. Objective. The aim of the study is to evaluate changes in the timeliness of vaccination in children of two subjects of Russian Federation with low immunization rates according to 2020 data. Methods. Immunization of children born in 2015-2017 and 2020-2022 were studied according to the form of federal statistical monitoring (FFSM) No. 6 and vaccination record cards (form No. 063/y) obtained from children's polyclinics of the Republic of Bashkortostan (two in 2020 and three in 2023) and the Republic of Sakha (Yakutia) (two in 2020 and four in 2023). The vaccination timeliness among children against infections from the national immunization schedule (NIS) list was determined. The timeliness of vaccination was evaluated by the proportion of children who received the required number of vaccine doses against each of the infection from the NIS list by the decreed age among all persons of the decreed age. Results. Data from 998 records was analyzed. The increase in timely vaccination against all vaccine-controlled infections in children was revealed. The proportion of children vaccinated according to the NIS has increased by 1.5-4 times. Timely vaccination of 95% children in the decreed age (by FFSM No. 6) was achieved in the Republic of Sakha (Yakutia) against tuberculosis, hepatitis B, measles, rubella, and mumps, and in the Republic of Bashkortostan against measles, rubella, and mumps. The increase in the multivalent vaccines' usage and simultaneous administration of several vaccines has been discovered. Conclusion. Monitoring the level of documented immunization and timely vaccination in children allows effectively control routine immunization quality. Implementation of multivalent vaccines and simultaneous administration of several vaccines in routine immunization provides radical change in the vaccination rate in pediatric population.